A variety of solid-state fluorescence properties of pyrazine dyes depending on terminal substituents. (November 2017) - Hirosawa, Risa; Akune, Yoko; Endo, Natsuko; Hatano, Sayumi; Hosokai, Takuya; Sato, Hiroyasu; Matsumoto, Shinya
Abstract: The optical properties of 2, 5-diamino-3, 6-dicyanopyrazine derivatives bearing singly methyl- or halogen-substituted benzyl groups were studied in both solution and crystalline phases. In solution, all derivatives showed similar absorption and fluorescence properties, since the electronic state of their fluorophore was not altered by substituents attached to the benzyl groups. In contrast, crystalline compounds exhibited a variety of fluorescence colours (yellow, orange, and red), since their solid-state absorption and fluorescence properties were correlated with a change in the electron-donating ability of amino groups due to crystallisation. The absolute fluorescence quantum yields of crystalline dyes (0.14–0.91) showed broad variability, depending on the nature and positions of terminal substituents. Graphical abstract: Highlights: Optical properties of 2, 5-diamino-3, 6-dicyanopyrazine derivatives were studied. Absorption and fluorescence maxima were dependent on amino group geometries. Indirect introduction of halogen atoms caused highly efficient crystal fluorescence. Terminal chlorine atoms played an important role in suppressing non-radiative decay.